2022
DOI: 10.18332/ejm/150354
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of stillbirth among women who gave birth at Hiwot Fana Specialized University Hospital, Harar, eastern Ethiopia

Abstract: INTRODUCTION According to WHO, there are nearly 2 million stillbirths every year, one every 16 seconds. The objective of our study was to assess the frequency and associated factors of stillbirth among women who gave birth at Hiwot Fana Specialized University Hospital, Harar, eastern Ethiopia, 2021. METHODS An institution-based retrospective cross-sectional study of medical records was conducted among 336 women who gave birth from 1 January 2020 to 31 December 2020. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This may be because women who live in rural areas may have di culty getting to medical facilities. The studies in Cameroon (17) and Nigeria (13) showed no difference between rural and urban residence.…”
Section: Discussionmentioning
confidence: 90%
“…This may be because women who live in rural areas may have di culty getting to medical facilities. The studies in Cameroon (17) and Nigeria (13) showed no difference between rural and urban residence.…”
Section: Discussionmentioning
confidence: 90%
“…This may be because women who live in rural areas may have difficulty getting to medical facilities. The studies in Cameroon [ 17 ] and Nigeria [ 13 ] showed no difference between rural and urban residence.…”
Section: Discussionmentioning
confidence: 99%